Topologi dan Kajian Kinerja Multi Konverter Arus Searah untuk Multi Generator-Hidro Mini - Rizki Nurilyas Ahmad; Mochammad Facta; Iwan Setiawan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
Energy wasted in the household streams can be easily found in the water faucets, showers, toilet sprinkles, and other equipment in plumbing systems where water only flows to clean out before it becomes a waste substance. Energy from flowing waters can be collected and converted to more useful forms of energy like electricity as it can be immediately utilized or stored. In the further development of the mini compact turbine generator (MCTG), the water flowing through every part of the house plumbing system is intended to be collected as electrical power. Unfortunately, the voltage produced by the conventional MCTG is insufficient for immediate applications in various electrical devices. In addition, the generated voltage does not conform to the voltage rating of the battery’s terminal as a medium for storing electrical energy. This research proposes the performance improvement of the MCTG output to produce a higher voltage by adding a DC boost converter, which can operate in a single or cascaded configuration to address issues with the MCTG output voltage and the boost converter’s efficiency when operating in high duty cycle values. Designs and simulations were conducted to obtain the expected criteria for electrical voltage generation. Several topologies tested included the single converter system, cascaded converter system, cascaded converter system with a selector, and parallel system. The results demonstrated that the parallel system worked better than the three topologies as it could yield voltage according to the reference voltage of 14 V and efficiency above 0.9 on the broader range of rotations of the MCTG rotor shaft.